Penerapan Keadilan Restoratif dalam Penyelesaian Kasus Kekerasan Rumah Tangga terhadap Anak - Zamaya, Zarman; Zahri, Saipuddin; Suharyono, Suharyono (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the application of restorative justice in resolving domestic violence cases against children in Indonesia. Domestic violence against children is a serious problem that continues to increase every year, requiring a legal approach that not only punishes perpetrators but also focuses on victim recovery and family harmony restoration. This research uses normative juridical method with statutory and conceptual approaches. The results show that restorative justice can be applied in domestic violence cases against children based on Supreme Court Regulation Number 1 of 2024, Police Regulation Number 8 of 2021, and Attorney General Regulation Number 15 of 2020. However, its application must consider the power relations between perpetrators and victims, the severity of violence, and the child's best interests. This study concludes that restorative justice can be an effective alternative in resolving domestic violence cases against children as long as it prioritizes victim recovery, involves child protection institutions, and does not neglect legal accountability. Recommendations include the need for clear guidelines for applying restorative justice in domestic violence cases against children and strengthening the capacity of law enforcement officer.